DEFENDING HUMAN RIGHTS IN THE ERA OF DATAFICATION - Normark, Maria; Hansson, Karin; Jacobsson, Mattias (AoIR Selected Papers of Internet Research, 2023)
In this paper, we explore how activists and human rights defenders deal with datafication. This work demonstrates how data can be a valuable resource in activism and campaign planning. In addition, data and lack of data also complicate daily life for people in vulnerable positions, for example, when contacting government agencies, schools, and medical facilities .Data from four types of human rights activism formed the basis of our analysis. They include volunteers and employees of NGOs dealing with refugee and migrant issues, homelessness, poverty, sexual minorities, and women's shelters. The study was done in Sweden, where the GDPR (General Data Protection Regulation) laws limit the handling and storage of personal data.The following five major themes emerge from the analysis of data from our interview study: Affording personal integrity, Data poverty, Protective data practices, Drawing attention to data, and Systems and data routines.In addition, this study shows how activists and the organizations that they support are exposed to contradictory aspects of data; on one hand, deliberately exposing data about marginalized/minoritized groups, while on the other, making sure those groups, along with activists themselves, are not exposed. Most important, the data laws and regulations are not adjusted to the needs of the most vulnerable in society, and therefore, actions of civil disobedience are necessary to care for vulnerable populations through data.